2018
DOI: 10.1080/14616742.2018.1487772
|View full text |Cite
|
Sign up to set email alerts
|

“A country to fall in love with/in”: gender and sexuality in Swedish Armed Forces’ marketing campaigns

Abstract: In 2010, Sweden abandoned its century-old military conscription in favour of an All-Volunteer Force (AVF). The Swedish Armed Forces (SAF) was now exposed to competition over labour, and soldiering was no longer a duty connected to male citizenship. It was a job among many.This thesis studies the SAF's efforts to cast the military organization as an attractive employer and public authority in the era of voluntarism. The aim is to contribute insights into how the Swedish population is called upon to identify as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 38 publications
0
37
0
3
Order By: Relevance
“…As a result of these representations, the army comes to be constructed as progressive. This is supported by Strand and Kehl's (2018) examination of Swedish Armed Forces advertising campaigns. They find that the Swedish Armed Forces are also portrayed as forward-thinking and that this reinforces and is reinforced by the conceptualization of national identity as progressive.…”
Section: The Positioning Of Women and People Of Colour As Equal To Whmentioning
confidence: 64%
See 2 more Smart Citations
“…As a result of these representations, the army comes to be constructed as progressive. This is supported by Strand and Kehl's (2018) examination of Swedish Armed Forces advertising campaigns. They find that the Swedish Armed Forces are also portrayed as forward-thinking and that this reinforces and is reinforced by the conceptualization of national identity as progressive.…”
Section: The Positioning Of Women and People Of Colour As Equal To Whmentioning
confidence: 64%
“…Other. As Strand and Kehl (2018: 1) put it, 'We argue that constructions of a tolerant and modern Sweden (re)produce treacherous, single narratives of distant and dangerous Others.' That is, presenting the self as progressive makes possible violent practices in the name of defending this way of life, which is taken to be a positive.…”
Section: The Uk Army Protects the Vulnerablementioning
confidence: 99%
See 1 more Smart Citation
“…It is often suggested that armed forces of liberal democracies govern citizens through a consumer market logic. Marketized military institutions are increasingly dependent on the capacity to attract and appeal to voluntary (rather than conscripted) recruits -but also to the broader public -in order to fill their ranks, secure resources and retain legitimacy for war preparations and deployments (Bailey, 2007;Cowen, 2006;Stahl, 2010;Strand and Kehl, 2019). Military sociologists have pointed specifically to the trend among liberal democracies to abandon conscription in favour of All-Volunteer Forces (AVFs), which in turn reduces the percentage of the public in direct contact with military institutions.…”
Section: Military Marketization and Digital Interactivitymentioning
confidence: 99%
“…Since around 2010, the SAF has worked resolutely to re-brand the institution through a range of traditional public relations and marketing techniques, but also, and increasingly, through digital outreach including social media campaigns (Strand and Kehl, 2019), milblogs (Hellman, 2015) and smartphone games (Stoehrel, 2013). This follows a broader trend where not only state militaries, but also private military and security companies (Schneiker et al, 2019) and arms producers (Jackson, 2017), increasingly rely on social media in their efforts to recruit both personnel and wider societal support.…”
Section: Military Marketization and Digital Interactivitymentioning
confidence: 99%